Analysis of Strategies and Challenges for The Development of Fiscal and Non-Fiscal Incentives in the Indonesia’s New Capital City (IKN) and Its Comparison to Other Economic Zones After the Implementation of PMK 136 of 2024 - Anwar, Muhammad Khoirul; Adrianto, Zaldy (Pertapsi-Indonesia collaborated with Petra Christian University, 2025)
The implementation of Global Minimum Tax (GMT) through Indonesia's Finance Minister Regulation No. 136/2024 has fundamentally transformed investment incentive strategies, particularly challenging traditional tax-based approaches used to attract foreign investment to Indonesia's New Capital City (IKN). This study analyzes strategies and challenges in developing fiscal and non-fiscal incentives in IKN post-GMT implementation and compares them with existing Special Economic Zones (KEK), Batam Zone, and Bonded Zones. The research employs descriptive qualitative methods through in-depth interviews with key stakeholders from the Directorate General of Taxes, Fiscal Policy Agency, tax practitioners, and academics, complemented by comprehensive literature review. Findings reveal Indonesia's strategic transformation from rate-based incentives toward GMT-compliant alternatives including Qualified Refundable Tax Credit (QRTC) and enhanced non-fiscal incentives such as regulatory simplification and infrastructure support. Key challenges include GMT regulatory complexity, inter-agency coordination limitations, and fiscal capacity constraints. IKN demonstrates competitive advantages through lowest investment thresholds, longest incentive duration, and most comprehensive incentive portfolio compared to other economic zones. This study provides the first comprehensive analysis of GMT adaptation in new capital city development, offering theoretical insights on international taxation policy and practical guidance for developing countries navigating similar challenges.